Adjunctive Er:YAG laser in non‐surgical periodontal therapy of patients with inadequately controlled type 2 diabetes mellitus: A split‐mouth randomized controlled study. (5th October 2021) - Feng, Chenchen; Ding, Yi; Tang, Liqin; Gui, Yong; Shen, Xiaoyun; He, Linlin; Lu, Xinyan; Leung, Wai Keung
Abstract: Background and Objective: Limited studies are available comparing the outcomes of non‐surgical periodontal therapy (NSPT) with or without adjunctive Er:YAG laser (ERL) in patients with type 2 diabetes mellitus (T2DM). This study evaluated the effects of ERL adjunctive NSPT on single‐rooted teeth of inadequately controlled T2DM patients with periodontitis. Methods: Twenty‐two inadequately controlled T2DM participants with periodontitis were recruited. Adopting a double‐blinded split‐mouth design and under block randomization, we investigated the effects of ERL in calculus removal then degranulation mode, or a sham treatment, adjunct NSPT, which included two visits of full‐mouth root surface debridement delivered within 4–10 days, to test or control single‐rooted teeth (Wuxi Stomatology Hospital, trial 2017‐016). We followed periodontal parameters (plaque %, bleeding on probing [BOP] %, probing pocket depth [PPD], probing attachment level [PAL]) and selected systemic parameters (fasting plasma glucose [FPG], glycosylated hemoglobin [HbA1c%], high sensitivity C‐reactive protein) at baseline, one, three, and six months after periodontal treatment. Results: The study was completed as planned. Periodontal parameters, FPG and HbA1c% of the 22 participants appeared significantly improved at six months ( p < 0.001). The 44 ERL treated, compared to 44 sham treated single‐rooted teeth exhibited significant improvement in BOP, mean PPD, and mean PAL at various postoperative follow‐up time points (effect size ≥0.44; p < 0.001). No adverse event was reported. Conclusion: Periodontal treatment outcomes in the T2DM patients with inadequate glycemic control were better in the single‐rooted teeth received ERL adjunct NSPT. Further studies are warranted to confirm the observations reported in this short‐term clinical study.